Pengaruh Fasilitas dan Lokasi terhadap Kepuasan Pengunjung Taman Cadika - Sinay, Kaleb Yusuf (Jurnal EMT KITA, 2026)
Cadika Park is a tourist attraction located in an urban area, which certainly influences visitor satisfaction. The level of tourist satisfaction can be measured through the influence of the facilities and location in the place. This study was conducted with a sample of 40 visitors selected using the Likert scale measurement method. The research instruments used included validity tests, reliability tests, and multiple linear regression analysis. The classical assumption tests carried out included normality tests, multicollinearity tests, and heteroscedasticity tests. Model feasibility tests were carried out using F tests, R² tests, and t tests. Data processing was carried out using Excel and SPSS software. The results showed that facilities partially had a positive and significant influence on visitor satisfaction with a calculated t-value > t-table (7.187 > 2.026). Location also partially had a positive and significant influence on visitor satisfaction with a calculated t-value > t-table (3.546 > 2.026). Simultaneously, facilities and location have a positive and significant effect on visitor satisfaction, with the calculated F-value > F-table (112.911 > 3.24). Facilities and location simultaneously contribute 85.9% to visitor satisfaction at Cadika Park.
Keywords: Facilities; Price; Satisfaction